Nutritional Requirements for Florida Sugarcane - Ronald W. Rice; Robert A. Gilbert; J. Mabry McCray (EDIS, 2010)
Revised! SS-AGR-228, an 8-page fact sheet by R. W. Rice, R. A. Gilbert, and J. M. MCray, provides an overview of plant nutrition, with general guidelines and deficiency symptoms for each nutrient for sugarcane production in Florida. Includes references. Published by the UF Department of Agronomy, March 2010.